PENGUJIAN KUALITAS PIGMEN ANTOSIANIN PADA BUNGA SENDUDUK(Melastoma malabathricum L.) DENGAN PENAMBAHAN PELARUT ORGANIK DAN ASAM YANG BERBEDA - Indang Julita; Mayta Novaliza Isda; Wahyu Lestari (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Anthocyanin is red, purple and blue pigment that is commonly found in plants and can be used as a natural dye. One of plant species that can be extracted as natural dye source and contains anthocyanin is senduduk (Melastoma malabathricum L.). The objective of this study was to compare the effectivenes of various solvents and organic acids in extraction process of antocyanin pigment from senduduk flower. The results showed that the color of anthocyanin extracts that produce the strongest color was found in 3% ethanol and 1% tartaric acid treatment, while the weakest color was found in 3% ethanol treatment. Low pH was produced in 3% ethanol + 1% tartaric acid, while high pH was produced in 3% ethanol treatment.